65. MINIMALLY INVASIVE CAROTID ENDARTERECTOMY: OPERATION PROCEDURE (Vietnam Journal of Community Medicine, 2024)
Carotid artery stenosis is one of the commonest causes of stroke, We can prevent affected stroke due to carotid stenosis by early dianosis and prompted management. Recently, new guide line for management carotid stenosis in elderly patients have been published.The value of carotid endarterectomy (CEA) has been well established in patients with symptomatic and asymptomatic carotid artery stenosis. Minimally invasive carotid endarterectomy has been performed in many vascular centers..There are many randomised controlled trials recently with large patients and long- term follow-up that have been published. Many new recommendations have been annouced by European Society for Vascular Surgery (ESVS), American Heart Association (AHA), European Stroke Organisation (ESO).Colour Duplex ultrasound (DUS) is the first line imaging modality due to low cost and accessibility and there are consensus criteria for diagnosing stenosis severity.A combination of two imaging modalities (DUS + CTA or DUS + MRA) improves accuracy and is routine practice in many center before CEA or CAS.Patients with an asymptomatic 60-99% stenosis, carotid endarterectomy should be considered in the presence of one or more imaging or clinical characteristics that may be associated with an increased risk of late stroke, provided 30 day stroke/death rates are < 3% and patient life expectancy exceeds five years.Patients have experienced a carotid territory transient ischaemic attack or ischaemic stroke within the preceding 6 months in association with a 70-99% carotid stenosis, it is recomended for carotid endarterectomy rather than carotid artery stenting provided the documented 30 day risk of death/stroke is
Keywords: Carotid stenosis; stroke; carotid edaretectomy; carotid artery stent; minimally invasive carotid endarterectomy